The presence of bacteria on periodontal ligament cells in different storage environments for teeth after displacement from the alveolar bone: preliminary in vitro research results - Phan, Anh Chi; Le, Thi Thu Nga; Tran, Thi Thanh Ngan; Le, Thi Bao Chi (Tạp chí Y Dược Huế, 2025)
Introduction: Teeth displaced from their alveolar bone can be replanted if properly handled and stored in suitable environments. To help minimize the failure of reimplantation, teeth should be preserved in a storage environment that is initially free of bacteria. Research objective: Evaluating the morphology of bacteria on the periodontal ligament cells in different storage environments at various time points after the teeth have been removed from the alveolar bone using Gram staining. Materials and Methods: An in vitro study without a control group was conducted using 48 premolars and third molars after extraction, which were stored in four environments: Dulbecco’s modified Eagle’s medium (DMEM), fresh whole milk (unsweetened), saline solution, and electrolyte-replenishing drink. The presence of bacteria was assessed at four time points: 30 minutes, 1 hour, 2 hours, and 24 hours. Results: In DMEM and fresh whole milk, Gram-positive cocci, Gram-positive bacilli, and Gram-negative bacilli were presented at 30 minutes, 1 hour, and 2 hours; by 24 hours, Gram-negative cocci were also presented. In the saline solution, Gram-positive cocci and bacilli were also presented at all time points; Gram-negative bacilli appeared at 2 and 24 hours. In the electrolyte-replenishing drink, Gram-positive cocci were the only bacteria found at all time points. Conclusion: Bacteria were presented on the periodontal ligament cells of the root surface in all four environments and at all four-time points of storage. However, at different time points, the number of bacterial groups found in DMEM and fresh whole milk was the highest and nearly equivalent, followed by the saline solution and the lowest count in the electrolyte-replenishing drink.